“Causality Of Fraud Detection Of Financial Statements By Auditors In Public Accounting Firm With Audit Quality As A Intervening Variable” - Hamilah Hamilah; Amrizal Sutan Kayo; Fajri Nuryono; Henni Handari (Brilliant International Journal Of Management And Tourism, 2022)
This research intends to test and analyze the effect of competence, independence and professionalism through audit quality on fraud detection by the Auditor at the Public Accounting Firm in DKI Jakarta in 2022. The sampling technique is through purposive sampling with multistage random sampling of 81 Auditors with 10 (ten) ) KAPA, which is then processed with Smart-PLS. Previous studies only used a purposive random sampling technique on KAP at random. The results of the tests in this study indicate that competence, independence and professionalism have a positive and significant effect on audit quality. Audit quality has a positive and significant effect on fraud detection. Furthermore, competence, independence and professionalism have a positive and significant impact on fraud detection. The path analysis test also shows that competence, independence and professionalism have a positive and significant effect on fraud detection through audit quality. These three variables show a positive and significant influence on fraud detection through audit quality, so the three minimum attitudes must be applied by the auditor to create a capable audit quality and be able to detect forms of fraud in financial statements.